The Speaking Difficulties Encountered by Non-English Students in Language Classroom - Rima Rahmaniah; Asbah Asbah (Muhammadiyah University of Mataram, 2018)
This research, entitled “The Difficulties Encountered by Non-English Department Students in Speaking English,” was a study at the Faculty of Teacher Training and Education Muhammadiyah University of Mataram. It was conducted to investigate difficulties encountered by Non-English Department students in speaking. The participants were 15 students from the second semester of Indonesian Department Muhammadiyah University of Mataram. It also aims to investigate the factors which are face by Non-English department students in Speaking English. This research used descriptive quantitative approach. Based on the data from test the difficulties encountered by a second-year student of Indonesian department are first was from the grammar aspect, there were 80% of students almost entirely inaccurate expect in stock phrases. Second, fluency aspect, there were 73% speech is very slow and uneven except, for short or routine sentences. Third, it is the pronunciation aspect; there were 73% of students gross error, and very heavy accent makes understanding difficult require frequent repetition. Fourth is from the vocabulary aspect there were 60% of students their vocabulary limited to basic personal and survival areas. The last it is from comprehension aspect there 55% of students understand only slow, very simple speech on common social and touristic topics; requires constant repetition and rephrasing. Factors were faced by Non-English department student in speaking English there are two factors, from internal factors and external factors. Internal factors such as they are a quiet person; they are hard to learn, difficult to remember vocabulary, difficult to pronounce the word, lack of grammatical mastery, they are lazy to memorize vocabulary, they are lack of confidence and fear of making a mistake. From external factors, they are seldom speaking English in the class, and their environment is not used English, and they prefer to use their mother tongue.